An assessment of Islamic financial institution and investor exposure to maritime assets - Abdullah, Adam; Hassan, Rusni; Kassim, Salina (International Economic Society, 2017)
The aim of this paper is to investigate the overall exposure of Islamic Financial Institutions involving retail and institutional investors to international maritime assets in order to facilitate Islamic equity finance and investment by Islamic finance institutions involving retail and institutional investors. Shipping is a strong growth industry with about 84% of global trade carried by the international shipping industry. However, shipping is a highly capital intensive industry and currently 75% of ship lending has been conducted by European banks and financed on a conventional basis. This study analyses the extent of Islamic investment and finance in international shipping. Our findings reveal that whilst Middle Eastern Islamic financial institutions have embraced financing of maritime assets, Malaysian institution have little or no exposure to international shipping. However, in terms of substance over form, Middle Eastern investors have structured debt ship-finance transactions to ensure fixed-income, rather than fully accept equity risk and returns. The significance is that Islamic equity finance, rather than structure debt finance, should increase the development of international shipping by Islamic financial institutions and investors.